If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + x + 3 = 7 Reorder the terms: -5 + 3 + x = 7 Combine like terms: -5 + 3 = -2 -2 + x = 7 Solving -2 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 7 + 2 Combine like terms: -2 + 2 = 0 0 + x = 7 + 2 x = 7 + 2 Combine like terms: 7 + 2 = 9 x = 9 Simplifying x = 9
| 10-2x-6=-x+5 | | (8*20)2+(8*13)2-(5*3)3-(7*2)= | | 50-2x=16x+16 | | 6x+6=106-10x | | 12x^2+19x=-5 | | (8*20)2+(8*13)2=X | | -7-9w=-7w-10 | | -5-6=-4x-(x+6) | | 9-x-2x=0 | | -5-6=-4-(x+6) | | (8*20)2=x | | N-15=22 | | x+3=40 | | 952=12d+28 | | 7x-4-3x=4x+8 | | -(7x-2)+5=3 | | 38-18=4(x-6) | | x-84=-0.5 | | h(t)=-2t^2+6t+3.5 | | x+5=-55 | | 5+x=5-x | | -2(x+6)=6 | | 13-10x=85-24x | | 9x-85=6x-10 | | 15x^2-13x-44=0 | | (253+x)=.55*(468+x) | | ln^2x-9=0 | | 6n+11=3n-7 | | 54-2x=7x+23 | | 3x=-3x+3 | | H(h+3)=130 | | 56-4x=14x+16 |